Spiritualitas Agama bagi Bencana Kemanusiaan dalam Filsafat Perenial: Tinjauan Pemikiran Filsafat Seyyed Hossein Nasr - Arip Budiman; Putri Anditasari (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2021)
This study aims to discuss the review of Seyyed Hossein Nasr's philosophical thoughts, regarding the spirituality of religion for humanitarian disasters. This research method applies a qualitative method through literature study and content analysis. The results and discussion found that the modern scientific paradigm that puts too much emphasis on the aspect ratio and ignores the spiritual aspect has an impact on human greed in managing natural resources which has an impact on the ecological crisis. The conclusion of this study is Nasr assume the religious spirituality for humanitarian disasters is a spiritual source of Islam. Al-Quran and Hadith become the spiritual basis to love and care to the universe, as a manifestation to get God’s love. Nasr assume that nature is a holy place that can be the manifestation of God’s light. Awareness of knowledge is not separate from Allah, becomes an important point for wise human spirituality.